Los Angeles Family and Neighborhood Survey (L.A.FANS), Wave 1, Public Data, 2000-2001 - Pebley, Anne R. ([Verlag nicht ermittelbar], 2019)
This study includes public user data files of two waves of interviews with L.A.FANS respondents. There often are multiple respondents in L.A.FANS households and Wave 2 includes both panel respondents and a new sample. Users' Guides which explain the design and how to use the sample are available for Wave 1 and Wave 2 at the RAND website. The Los Angeles Family and Neighborhood Survey (L.A.FANS) is a two-wave study of adults and children in Los Angeles County and of the neighborhoods in which they live. The first wave (L.A.FANS-1), which was fielded between April 2000 and January 2002, interviewed adults and children living in 3,085 households in a stratified probability sample of 65 neighborhoods throughout Los Angeles County. The samples of neighborhoods and individuals were representative of neighborhoods and residents of Los Angeles County. Poorer neighborhoods and households with children were oversampled. In Wave 2 of L.A.FANS (L.A.FANS-2), Wave 1 respondents living in Los Angeles County were reinterviewed and updated information was collected on Wave 1 respondents who had moved away from Los Angeles County. A sample of individuals who moved into each sampled neighborhood between Waves 1 and 2 was also interviewed, for a total of 2,319 adults and 1,382 children (ages less than 18 years). Additional information on the project is available at the RAND website. Additional information on the project, survey design, sample, and variables are available from: Sastry, Narayan, Bonnie Ghosh-Dastidar, John Adams, and Anne R. Pebley (2006). The Design of a Multilevel Survey of Children, Families, and Communities: The Los Angeles Family and Neighborhood Survey, Social Science Research, Volume 35, Number 4, Pages 1000-1024 The Users' Guides (Wave 1 and Wave 2) RAND Documentation Reports page